OPPORTUNITIES FOR EARLY OUTPATIENT DIAGNOSTICS OF OBSTRUCTIVE SLEEP DISORDERED BREATHING - V. N. Larina; T. N. Mironova; E. M. Elfimova; T. A. Alekseeva; I. V. Starostin; V. P. Sidorova; A. Yu. Litvin (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To evaluate the prevalence of possible obstructive respiratory disorder during sleep in outpatients by the data from computed monitoring pulse oxymetry (CPO) and questionnaires.Material and methods. To the open one stage non-randomized comparative study, 175 patients included: 37,1% males, 62,9% females, age 55,1±11,1 y.o., visiting a clinician office at outpatient facility. Sleep disordered breathing of obstructive origin was diagnosed with a survey, modified Stradling questionnaire and CPO; and excessive daytime sleepiness — with Epworth score. For confirmation of obstructive sleep apnea (OSA), a bifunctional monitoring was performed (BM) with further comparison of the data with CPO results.Results. Chronic hypoxemia at night by CPO was found in 71,4% patients, and probability of OSA moderate and severe — in 42,8% patients. By the modified Stradling, OSA was predicted in 57,7%, by Epworth, the daytime sleepiness was found in 11,4%. Mild OSA in BM was found in 8,9%, moderate — 14,7%, severe — 20,6%. The data from CPO matched with BM in 80% patients. Sensitivity of CPO for nocturnal hypoxemia of various severity was 92,4%, specificity — 76,4%; sensitivity of the Stradling questionnaire — 88,9%, specificity — 88,2%. Sensitivity of Epworth score — 27,8%, specificity — 82,4%.Conclusion. Chronic nocturnal hypoxemia was found in 71,4%, and probability of moderate and severe OSA — in 42,8% in outpatients with internal diseases profile. CPO and Stradling questionnaire can be applied as diagnostic instruments for OSA at outpatient stage.